Fall Worry Restricts Social Engagement in Older Adults. (June 2020) - Choi, Namkee G.; Bruce, Martha L.; DiNitto, Diana M.; Marti, C. Nathan; Kunik, Mark E.
Objective: To examine cross-sectional and longitudinal associations between (a) activity-limiting fall worry (ALW) and (b) self-reported health-related restrictions and social engagement among older adults.Method : The National Health and Aging Trends Study Waves 5 (T1) and 6 (T2) provided data ( n = 6, 279). Binary and multinomial logistic regression models were used to examine association of T2 social engagement restrictions with T2 fall worry and association of T1–T2 changes in social engagement restrictions with T1–T2 changes in fall worry.Results : ALW was significantly associated with both informal and formal social engagement restriction at T2. Onset of ALW and continued ALW between T1 and T2 were also significantly associated with newly reported restrictions in both informal and formal social engagement at T2 even controlling for falls incidents and changes in health status and other covariates.Discussion : The findings underscore the importance of reducing fall worry and preventing social disengagement in late life.